THE EFFECT OF ANIMATION VIDEOS ON YOUNG LEARNERS’ VOCABULARY AT GRADE 4 IN SDN 2 PALAPA BANDAR LAMPUNG - Deri Sis Nanda; Sugiono Sugiono (Universitas Bandar Lampung, 2020)
A purpose of this research to determine the effect of animation video on young learnersvocabulary grade 4 in SDN 2 Palapa Bandar Lampung. It was quantitative research to aimetwo classe were experiment and control class in using treatment five meetings. The researchdesign used pretest to determine ability of young learners to learn English vocabulary. Thepopulation was grade IVA and IVB. The researcher chose two classes on test instrument,there were twenty five multiple choice questions to use pretest-posttest. The result beforegiving treatmen mean value was 69.2000 obtained by experiment class and mean value was69.600 obtained by control class so two class had same ability level. Researcher gaveposttest after it finished to give treatment and analyze of SPSS showed t-test was 0.05English vocabulary. Mean score was 84.8000 experiment class and mean score was77.2000 control class. There was an effect on treatment that it had been given byresearcher, (.000) was lower than (<0.05), and it was mean the treatment to animationvideos was significant of calculation procedure, so it was calculation animation videoscould improve English vocabulary of young learners and it could be recommendation asteaching media.